The Use Of Fintech Technology In Islamic Banking: Challenges And Opportunities For Financial Industry Growth - Pardi, Abisar (IAIN Kendari, 2024)
Fintech technology has the potential to increase access to Islamic financial services, improve the operational efficiency of the Islamic financial industry, and encourage innovation in Islamic financial products and services. However, to realize this potential, the Islamic financial industry needs to address the challenges that exist, such as Sharia compliance, regulation, and customer awareness. The Islamic financial industry needs to strengthen the implementation of Sharia principles in fintech products and services. By addressing these challenges, the Islamic financial industry can leverage the potential of fintech technology to increase Islamic financial inclusion in Indonesia.